Proceedings of the 2007 International Symposium on Low Power Electronics and Design 2007
DOI: 10.1145/1283780.1283808
|View full text |Cite
|
Sign up to set email alerts
|

Towards a software approach to mitigate voltage emergencies

Abstract: Increases in peak current draw and reductions in the operating voltages of processors continue to amplify the importance of dealing with voltage fluctuations in processors. One approach suggested has been to not only react to these fluctuations but also attempt to eliminate future occurrences of these fluctuations by dynamically modifying the executing program. This paper investigates the potential of a very simple dynamic scheme to appreciably reduce the number of run-time voltage emergencies. It shows that w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 10 publications
(17 reference statements)
0
28
0
Order By: Relevance
“…We have previously shown that there is a strong correlation between voltage violations and microarchitectural events [9]. A variety of events can lead to emergencies such as cache misses, pipeline flushes due to branch misprediction, TLB misses, and longlatency events.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that there is a strong correlation between voltage violations and microarchitectural events [9]. A variety of events can lead to emergencies such as cache misses, pipeline flushes due to branch misprediction, TLB misses, and longlatency events.…”
Section: Introductionmentioning
confidence: 99%
“…A number of papers dealt with mitigating voltage droops using software techniques [4][5] [16]. These techniques recognize the existence of repetitive code with high di/dt transition activity and dampen or eliminate this activity through software techniques.…”
Section: Previous Workmentioning
confidence: 99%
“…However, most of these studies focused on prevention/avoidance [6][8], mitigation [12] [13], or recovery from the di/dt effect [10] [11]. In contrast, there are three previous works on creation of di/dt stressmarks to maximize voltage droop.…”
Section: Related Workmentioning
confidence: 99%